Use simultaneous equations:
2x + 7 = x^2 + 8x - 9
7 = x^2 + 6x - 9
16 = x^2 + 6x
+ or - 4 = 7x
answer is
-4/7 or 4/7
Answer:
18 inches
Step-by-step explanation:
volume = lenght * width * depth
let the depth be x
32400=60*30*x
x=32400/(60*30)
x=32400/1800
x=18
Answer:
(-13,-4)
Step-by-step explanation:
4x-8y=-20
9x+113=y
Substitute in y for 9x+113
4x-8y=-20
Substitute
4x-8(9x+113)=-20
Simplify
4x-72x-904=-20
Simplify
-68x-904=-20
Additive Prop. of Equality
-68x-904+904=-20+904
Simplify
-68x=884
Isolate the variable(x)
<u>-68x</u>=<u>884</u>
-68x -68x
Simplify
x=-13
Solve for y
9x+113=y
9(-13)+113=y
-117+113=y
-4=y
Check
4x-8y=-20
4(-13)-8(-4)=-20
-52+32=-20
-20=-20
9x+113=y
9(-13)+113=-4
-117+113=-4
-4=-4
Hey there!
It seems your problem is simply trying to rewrite the sentence.
Let's rewrite our sentence, from the phrase after the comma to the phrase before the comma.
Essentially, we are just flipping the sentence structure.
It should be this:
The two angles are complementary if the sum of the two angles are 90 degrees.
Let's take a good look at our answers.
A.) There are two angles.
While this is a true statement, it's a little too vague to understand. We can eliminate this answer choice.
B.) The sum of two angles is 90 degrees.
This is also a true statement, but it doesn't describe what type of angles sum to 90 degrees, so we can eliminate this as well.
C.) The angles are complementary.
This is similar to answer choice A. It's a little too vague for specific understanding. We can eliminate this answer choice.
D.) Angles are complementary if their sum is 90 degrees.
This is an accurate statement, and provides details to support it's claim, also rewriting the original sentences into one properly. This answer choice is correct.
Your answer is D.)
I hope this helps!
Answer:
(b³+11b²+24)ft³
Step-by-step explanation:
Volume of the rectangular prism = Length * Width * Height
Given the dimension
Length = b+8 ft
Width = b ft
Height = (b+3)ft
Volume of the rectangular prism = b(b+8)(b+3)
Volume of the rectangular prism = b(b^2+3b+8b+24)
Volume of the rectangular prism = b(b^2+11b+24)
Volume of the rectangular prism = b(b^2)+b(11b)+1(24)
Volume of the rectangular prism = b^3+11b^2+24
Hence the Volume of the rectangular prism is (b³+11b²+24)ft³